THE IMPACT OF MINING ACTIVITIES ON THE WEST OF PETROŞANI DEPRESSION AND IDENTIFICATION OF AFFECTED GEOMORPHOLOGICAL RESOURCES. CASE STUDY: ANINOASA-VULCAN-LUPENI SECTOR - NIMARĂ, N.; TOFAN, G. B. (Studia Universitatis Babeș-Bolyai Geographia, 2015)
The Impact of Mining Activities on the West of Petroşani Depression and Identification of Affected Geomorphological Resources. Case Study: Aninoasa-Vulcan-Lupeni Sector. The west region of Petroşani Depression, like the whole depression, suffered some changes in the geomorphologic environment as a result of coal mining activities. Following displacement processes of mass materials and relocation of it, changes in shape are brought to the original territory that contrast with the natural landscape. The human impact on the West of Petroşani Depression and hence to the analyzed sector is especially highlighted as it materializes into waste dumps and coal pits.